Conversational Markers in Government-provided Interpretation Services: A Matter of Omissions and Additions - Vargas-Urpi, Mireia (Íkala, Revista de Lenguaje y Cultura, 2017)
According to Wang (2013, p. 130), conversational markers are linguistic elements performing a double role: informational and interactive. In their second role, they are used to regulate interaction between participants in a conversation, in transitioning to another topic, when stating speaker’s attitude, and so on. Therefore, they perform a significant role in any oral exchange. However, what does it happen to conversational markers when that oral exchange is made possible by an interpreter? In research on public service interpreting, the study of conversational markers has been rather anecdotal and, unless some exceptions within the judicial sphere, our knowledge on the treatment this discourse markers receive in interpreting is scarce. This paper presents the study of a conversation interpreted by a mediator-interpreter in public services in the language pair Chinese-Catalan, which was recorded and subsequently transcribed verbatim in order to make analysis easier. The results reflect la omission of all conversational markers the primary interlocutors (a high school teacher and a Chinese student’s mother) had been using, as well as the addition, by the mediator-interpreter, of conversational markers that were absent in the original message. In the conclusions, I reflect upon the potential implications of these results, and on the prospective value of this study.